Comparative study of the selected methods of laryngeal tone determination - W. Wszołek; M. Kłaczyński (Archives of Acoustics, 2014)
Laryngeal tone (pitch), understood as fundamental frequency of the voice ($F_0$), is one of the most important features in the field of acoustic studies of the speech signal. Time dependence of the laryngeal tone contains very essential information, providing a basis for speech recognition and extraction of distinctive features in the voice signal. The parameters of the laryngeal tone also contain some features that are useful in the medical diagnosis and therapy. Detailed knowledge of the laryngeal tone enables also both qualitative and quantitative analysis of speech deformations, related to pathological changes in the larynx area. Due to the progress in professional methods of registration and processing of acoustic signals, several algorithms for determination of laryngeal tone have been developed. Yet an accurate and detailed determination of the laryngeal tone characteristics for a given speaker still presents a problem in the field of speech signal analysis. In the present paper selected methods of $F_0$ determination have been described and compared.